Sociologia, cultura e arte: um debate entre espaços e tempos - Eliska Altmann (Ciências Sociais Unisinos)
Based on the volumes of the Brazilian anthropologist Gilberto Velho - Sociologia da arte; Sociologia da arte II; and Arte e sociedade - ensaios de sociologia da arte (1966, 1967 and 1977) - in light of the book A sociologia da arte (2008), of the French sociologist Nathalie Heinich, the article highlights Brazilian publications comprising thinkers of sociology of art and culture through space-time dialogues. Included in Velho's books and analyzed by Heinich, authors such as Erwin Panofsky, Jean Duvignaud, Pierre Francastel, and Roger Bastide will have their ideas analyzed, in order to verify whether or not there would be common aspects in their theoretical and methodological propositions and what their pertinence in the contemporary debate would be. The analysis of established assumptions, which comprehend art and social worlds, seeks a conceptual contribution and a current reflection on the field.